2021
DOI: 10.1038/s41398-021-01665-4
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression profiling in peripheral blood lymphocytes for major depression: preliminary cues from Chinese discordant sib-pair study

Abstract: The etiology of major depressive disorder (MDD) involves many factors such as heredity and environment. There are very few MDD-related studies in Chinese population using twin or sib-pairs for depression-control samples. Here we used the microarray approach and compared gene expression profiling of peripheral blood lymphocytes from 6 sib-pairs discordant on lifetime history of MDD. Within sib-pair differentially expressed genes are obvious fewer in the 1st, 2nd, and 5th compared with those in the 3rd, 4th, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…29 Genetic components have also been proved to contribute to cancer susceptibility. 30 For the proportion of cancer mortality by sex, we notice a significantly higher incidence of lung cancer mortality in male patients (39.3%) compared to female patients (18.9%). This disparity may be attributed to the prevalence of common risk factors for cardio-oncology diseases in males, such as smoking, which induces the alterations in lipid metabolism, and lead to atherosclerosis and plaque progression.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…29 Genetic components have also been proved to contribute to cancer susceptibility. 30 For the proportion of cancer mortality by sex, we notice a significantly higher incidence of lung cancer mortality in male patients (39.3%) compared to female patients (18.9%). This disparity may be attributed to the prevalence of common risk factors for cardio-oncology diseases in males, such as smoking, which induces the alterations in lipid metabolism, and lead to atherosclerosis and plaque progression.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, in the diagnosis and treatment for CAD patients, radiation exposure is inevitable and may increase the risk of carcinogenesis (like lung cancer), especially in patients who have received multiple CAG 29 . Genetic components have also been proved to contribute to cancer susceptibility 30 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we assumed that methylation levels in PBLs could reflect those of the brain cells, based on previous evidences. Indeed, it has been demonstrated that DNA methylation levels at PBLs mirror those of brain cells [ 30 , 31 ], at that for this reason PBLs can be used as reliable peripheral markers of psychiatric conditions, such as major depressive disorder [ 32 , 33 ]. Recently, the finding that blood–brain barrier permeability is increased in individuals with central nervous system diseases reinforces the idea that it is possible to retrieve in peripheral blood molecules originating from brain and this, in turn, facilitates the diagnosis of psychiatric/neurological disorders by the analysis of PBLs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a number of researches [30][31][32][33][34] demonstrated that alterations in DNA methylation in peripheral cells could reflect those occurring in brain cells, thus proving new opportunities for studying psychiatric disorders by investigating peripheral epigenetic markers of the illness [35,36]. Purpose of the present article is to compare front-line healthcare professionals versus the other healthcare workers in terms of mental health (depression and PTSD symptoms) and methylation levels of a panel of stress-related genes.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the immune-related phenotypes associated with MDD are the result of molecular and transcriptional alterations, as demonstrated in differences in blood mRNA gene expression. Previous research has shown that individuals with MDD have altered patterns of expression of immune-related genes compared with controls [25][26][27][28][29][30], but it is still unclear whether this altered immune-related gene expression is fully captured by CRP. For example, in a microarray study performed on 1848 subjects, Jansen and colleagues found 129 genes to be differentially regulated in MDD vs. controls, including genes involved in immune-related pathways, 127 of which were still significant after correction for CRP values [31].…”
Section: Introductionmentioning
confidence: 99%